Yield comparison of rice genotypes in humid and irrigated lowland - Soares, Plínio César; Sediyama, Carlos Sigueyuki; Cruz, Cosme Damião; Silva, José Carlos (Pesquisa Agropecuaria Brasileira, 1995)
Competition tests between F6 lines from two rice crosses selected the F4 generation were conducted in humid and irrigated lowland cultivation systems, for two years. From the F2 generation, segregating generations of each cross were conducted independently in each environment. The objectives were to verify if the same genotypes could be used for both cultivation systems and if only one environment could be used for preliminary selection of rice lines adapted to both cultivation systems, in order to reduce operational costs of lowland rice genetic improvement programs. The results showed that: 1) the same lines can be used indiscriminately in the humid lowland and in the irrigated lowland systems; and 2) in the selection of rices lines for lowland, the segregating populations can be conducted only in the irrigated condition, and then the final evaluations should be done in the irrigated and non irrigated conditions.